Credit information sharing, nonperforming loans and economic growth: A cross-country analysis - Khanh Hoang; Son Tran; Liem Nguyen (Cogent Economics & Finance)
Employing 3-Stage Least Squares (SLS) regression on the aggregate dataset of 120 countries from 2004 to 2017, this study is the first to investigate whether credit information sharing exerts impact on nonperforming loans of banking system and economic growth rate. First, our findings provide evidence of a negative association between bad debt levels and credit information sharing, suggesting that information sharing tends to enhance the financial sustainability of the banking sector. Furthermore, our study provides evidence in line with an indirect channel via which information sharing is conducive to economic growth: information sharing decreases the nonperforming loans, which hampers economic growth. This result remains unchanged due to the introduction of additional explanatory variables, as well as the use of an alternative dependent variable. Finally, policy implications are discussed based on the findings of the research.